1998
DOI: 10.1590/s0102-311x1998000700011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, cytogenetic and toxicological studies in rural workers exposed to pesticides in Botucatu, São Paulo, Brazil

Abstract: Pesticides can cause gene mutations and chromosomal aberrations in exposed individuals. We have investigated 24 workers exposed to pesticides. Clinical examinations and cytogenetic and toxicological tests were performed. Ten non-exposed individuals were used as controls. Toxicological dosages of copper, zinc and manganese (metals found in some pesticides), hepatic enzyme dosage (GOT, GPT, AR) and acetylcholinesterase activity were performed in 16 workers and 8 controls. In the exposed workers, the most relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
1
14
0
9
Order By: Relevance
“…Assim, aumentos significativos na incidência de aberrações cromossômicas e/ou no intercâmbio de cromátides irmãs, foram constatadas por De Ferrari et al (1991), em floricultores; por Kourakis et al (1992), em trabalhadores em casas de vegetação e por Carbonell et al (1995) e Bréga et al (1998), em trabalhadores de zonas rurais. Em relação aos micronú-cleos, sua freqüência acha-se significativamente aumentada nos floricultores italianos estudados por Bolognesi et al (1993), embora Scarpato et al (1996) relatem achados negativos em estudo semelhante.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Assim, aumentos significativos na incidência de aberrações cromossômicas e/ou no intercâmbio de cromátides irmãs, foram constatadas por De Ferrari et al (1991), em floricultores; por Kourakis et al (1992), em trabalhadores em casas de vegetação e por Carbonell et al (1995) e Bréga et al (1998), em trabalhadores de zonas rurais. Em relação aos micronú-cleos, sua freqüência acha-se significativamente aumentada nos floricultores italianos estudados por Bolognesi et al (1993), embora Scarpato et al (1996) relatem achados negativos em estudo semelhante.…”
Section: Discussionunclassified
“…Porém, vários estudos realizados em indiví-duos que mantiveram contato profissional com mistura de praguicidas em diversos países, indicaram a ocorrência de aberrações cromossô-micas (Bréga et al, 1998;Crossen et al, 1978;Nehèz et al, 1981;Shabtai et al, 1979;Yoder et al, 1973).…”
unclassified
“…Cytogenetic damage related to pesticide exposure has been reported in various populations. Some investigators have reported significant differences in the percentage of CAs in exposed individuals (range, 2.66-10.30%) compared with control (range, 0.53-5.52%) (Balaji and Sasikala 1993;Brega et al 1998;De Ferrari et al 1991;Joksic et al 1997; Kourakis et al 1992;Rupa and Reddi 1991;Yoder et al 1973); others have not (de Cassia Stocco et al 1982;Hoyos et al 1996;Steenland et al 1986).…”
mentioning
confidence: 99%
“…Erythrocyte acetylcholinesterase level is used as a marker to evaluate the exposure to organophosphates (Brega et al 1998;Gomes et al 1998;Lakew and Mekonnen 1998;Tinoco-Ojanguren and Halperin 1998). The inactivation of acetylcholinesterase causes overstimulation of the nervous system, which produces such symptoms as headache, dizziness, nausea, stomachache, and weakness (Ballantyne et al 1994;Dulout et al 1985).…”
mentioning
confidence: 99%
“…The effects can be seen on a short-or a long-term basis and the symptoms can vary from headache to cancer. Pesticides can cause gene mutations and chromosomal aberration in exposed individuals [1][2][3][4][5]. The primary targets of toxicity are the haematopoetic system (serum cholinesterase inhibition), the cardiovascular system (cardiovascular lesions, abnormalities in heart rate and increase in heart-to-body ratio, tachycardia, tachypnoea, sinus bradycardia, depression of ST segments with T-wave inversion, elevated blood pressure), the reproductive system (placental morphology, fibrosis and haemorrhage, and inhibition of DNA synthesis in seminiferous tubules) and the nervous system (headache, muscle weakness, insomnia, dizziness, impaired memory, miosis, fasciculation, neuralgia) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%